Facing America : iconography and the Civil War - Samuels, Shirley (Oxford University Press, 2004)
Exploring how the face and body of America were imagined both physically and metaphorically during the Civil War, this book shows how visual iconography affected changes in postbellum gendered and racialised identifications of the nation.